Preparing for the information society: a critical analysis of Uganda's broadcast policy in light of the principles of the WSIS - Namusoga, Sara (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
This study analyses Uganda's 2004 Broadcast Policy in light of the WSIS principles in order to establish whether the policy enables radio to build an inclusive and people-centred Information Society, and if so, in what ways it does this. The study specifically focuses on radio, which it views as the dominant medium in Uganda, and therefore the medium with the greatest potential to build a sustainable Information Society in the country. The study is informed by media policy theories as well as Information Society theories. It is argued that although most definitions of the Information Society consider the newer ICTs, especially the Internet, as the key drivers in the Information Society, most developing countries like Uganda are far from reaching the desired level of computer and Internet access as proposed by some Information Society theorists. Instead, most people in Uganda rely heavily on older ICTs, especially radio, for information about key issues in their daily lives. Inevitably, radio ends up being a key player in building the Information Society in these countries. The study, therefore, finds most of the common Information Society theories lacking and adopts the WSIS definition, which is more relevant to Uganda's situation. This study also maintains that if radio is to be a key player in building an inclusive and people-centred Information Society in Uganda, the 2004 Broadcast Policy has to create that enabling environment, by, for example, promoting public service radio through local content programming, and diversifying radio ownership. The data for this study was obtained using the qualitative research approach, and specifically the research tools of document analysis and individual in-depth interviews. The findings indicate that the policy's emphasis is on building a broadcast sector that addresses the public's interests through local content programming and provision of diversified media services. However, the study also found that the policy is vague on some very crucial aspects, which would benefit the public, namely, local content quotas and the independence of the public service broadcaster.
Keywords: World Summit on the Information Society; Broadcasting policy -- Uganda; Information society -- Uganda; Information technology -- Social aspects -- Uganda; Public broadcasting -- Uganda; Radio broadcasting policy -- Uganda; Radio -- Uganda; Mass media -- Uganda